Furnace for scientific research with temperature control using Peltier cells and a gas heat transference system: Design and building. (5th February 2023) - Correa, H.; Pineda S., R.; Lara, D. Peña
Abstract: A novel system was designed and built for scientific research to improve temperature control. The built system allows physical properties measurements ranging from room temperature to 400 ° C in a controlled atmosphere. It consists of a cylindrical furnace that uses a temperature control system based on Peltier effect cells and a gas heat transfer system that extracts heat from the inner of a heaters furnace and takes it out into the atmosphere of the environment. The experimental results show that the introduction of cooling strategies like Peltier cells and a gas heat transfer system allows for improving temperature control: managing quickly stabilizes the temperature at a fixed value, controls heating and cooling rate, improves response time, and rapidly decreases the temperature from high-temperature value to 25 ° C . A linear combination of exponential functions modeled the experimental results of heat flow. The built device shows good performance compared to when not using Peltier cells and a gas heat transfer system. Highlights: Novel system designed, built for scientific research improving temperature control. Furnace uses a cooling and temperature control system based on Peltier effect. Incorporating Peltier cells and gas heat transfer system improves control for heating/cooling. Technological advantage is performing rapid cooling from high temperatures.